Living with cystic fibrosis during the COVID-19 pandemic: An interpretive description of healthcare access from patients with cystic fibrosis and their providers in Alberta, Canada - Katelyn Brehon; Pam Hung; Maxi Miciak; Winnie M. Leung; Kadija Perreault; Douglas P. Gross; Jason Weatherald; Paul E. Ronksley; Michael K. Stickland; Grace Y. Lam (PLoS ONE, 2025)
Background The current study aimed to explore patient and provider perspectives of the impact of the pandemic on cystic fibrosis healthcare access and service delivery. Methods We used Interpretive Description, a qualitative approach with the end-goal of informing decisions and actions in clinical practice by generating findings that are clinically meaningful and useful. Levesque et al.’s “Conceptual framework of access to health care” informed the development of our interview guides. Interviews were conducted via telephone or Zoom and confidentially transcribed verbatim. Data generation and analysis occurred concurrently to allow for iterative refinements of the interview guides. Analysis was informed by Braun and Clarke’s six phases of reflexive thematic analysis. Strategies to enhance rigour and trustworthiness of the findings were utilized. Results We completed 13 interviews: 8 with patients and 5 with providers. Three key themes were generated: (a) Tensions due to infection prevention at micro- meso-, and macro- levels; (b) Modifying aspects of person-focused care can bolster perceived quality of clinical encounters; and (c) Accessibility of appropriate healthcare services could improve efficiency of service delivery. Infection prevention at the individual level was not found to be burdensome. Society’s compliance with public health measures, or lack thereof, impacted the level of stigma and anxiety experienced by patients with cystic fibrosis. A changed model of care reliant on patient self-report instead of clinician-led testing and in-person assessment due to the transition to virtual care was associated with mixed perceptions since patients with cystic fibrosis were comfortable making care decisions but many participants (patient and provider) felt challenged by the lack of objective data for decision-making. It was essential for patients with cystic fibrosis to feel known, heard, and seen by their providers in order to feel the care was effective. Finally, critical insights around the need for a balance of in-person and virtual care as well as the need for mental health supports were offered. Conclusions The learnings from this study could be translated into practical strategies for improving cystic fibrosis care during the pandemic and beyond. We recommend: (1) a hybrid approach to care moving forward, (2) each patient having a lead physician with others filling in as necessary when scheduling demands, and (3) a reallocation of resources to fund a mental health practitioner position.